Increasing Iron Status through Dietary Supplementation in Iron-Depleted, Sedentary Women Increases Endurance Performance at Both Near-Maximal and Submaximal Exercise Intensities. Issue 2 (10th January 2019) - Pompano, Laura M; Haas, Jere D
ABSTRACT: Background: Iron deficiency persists as the most common micronutrient deficiency globally, despite having known detrimental effects on physical performance. Although iron supplementation and aerobic exercise have been examined individually and are known to improve physical performance, the impact of simultaneous iron supplementation and aerobic training remains unclear. Objective: The aim of this study was to examine the individual and combined effects of iron supplementation and aerobic training on improving maximal and submaximal physical performance in iron-depleted, nonanemic (IDNA) women. We hypothesized that women receiving iron would improve their endurance performance but not their estimated maximal oxygen consumption (e V O2 max). Methods: Seventy-three sedentary, previously untrained IDNA (serum ferritin <25 µg/L and hemoglobin >110 g/L) women aged 18–26 y with a body mass index (kg/m 2 ) of 17–25 participated in a double-blind, 8-wk, randomized controlled trial with a 2 × 2 factorial design including iron supplementation (42 mg elemental Fe/d) or placebo and aerobic exercise training (5 d/wk for 25 min at 75–85% of age-predicted maximum heart rate) or no training. Linear models were used to examine relations between training, supplement, and changes in the primary outcomes of observed maximal oxygen consumption ( V O2 peak) and e V O2 max and ventilatory threshold (absolute oxygen consumption and percentage of maximum). Re-evaluation of a published meta-analysis was used to compare effects of iron supplementation on maximal oxygen consumption ( V O2 max) and V O2 peak. Results: There were significant training-by-supplement interactions for V O2 peak, volume of oxygen consumption at the ventilatory threshold, and the percentage of e V O2 max where the threshold occurred, with the iron-untrained group performing better than the placebo-untrained group. There was no beneficial effect of iron supplementation for V O2 max (mean difference: 0.53; 95% CI: −0.75, 1.81; P = 0.42), but a significant benefit was observed for V O2 peak (mean difference: 1.87; 95% CI: 0.15, 3.60; P = 0.03). Conclusions: Iron supplementation increases endurance performance at submaximal and maximal ( V O2 peak) exercise intensities in IDNA women. However, increasing iron status does not increase e V O2 max. This trial was registered at clinicaltrials.gov as NCT03002090.